Analysis Of Violence In Children During The Covid-19 Pandemic - Onny Fitriana Sitorus; Dony Darma Sagita; Novelia Utami (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
This research is a quantitative descriptive study, which thoroughly describes violence against children during the Covid-19 pandemic. The sample of this study was determined using the Non-Probability Sampling with the convenience sampling technique for 165 people. Based on the research results, the handling of violence against children includes 43% physical aspects, 38.8% psychological aspects and 18.2% neglect aspects. The form of treatment that often occurred with hitting amounted to 39.4% and was often done by fathers by 60.6% was a physical aspect. The role of parents, especially fathers, should educate so that children find good examples to be imitated, and the role of mothers as supervisors and provide advice to fathers in educating. Furthermore, researchers can formulate alternative solutions in answering the conditions that occur based on the results of this study through a follow-up study or research.